Mass-spectrometric studies of new 6-nitroquipazines—serotonin transporter inhibitors - Witowska-Jarosz, Janina (Springer-Verlag, 2011)
Six synthesized 6-nitroquipazine derivatives were examined by electron ionization (EI) and electrospray ionization (ESI) mass spectrometry in positive and negative ion mode. The compounds exhibit high affinity for the serotonin transporter (SERT) and belong to a new class of SERT inhibitors. The EI mass spectra registered in negative ion mode showed prominent molecular ions for all the compounds studied. All EI mass spectra and all ESI mass spectra showed similar fragmentation pathways of molecular ions, but the pathways differed between EI and ESI. The differences were explained with the aid of theoretical evaluation of the stability of the respective radical ions (EI MS) and protonated ions (ESI MS). [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00216-011-5410-8) contains supplementary material, which is available to authorized users.